Nonlinear analysis of fully coupled integrated spar-mooring line system - Jameel, Mohammed; Ahmad, Suhail; Islam, Abul Bashar Mohammad Saiful; Jumaat, Mohd Zamin (2011)
Oil and gas exploration have moved from shallow water to much deeper water far off the continental shelf. Spar platforms under deep water conditions are found to be the most economical and efficient type of offshore platform. The number of operational Spar platforms such as SB-1, Shells ESSCO, Brent Spar, Oryx Neptune Spar, Chevron Genesis Spar and Exxons Diana Spar in the Gulf of Mexico and North Sea prove the effectiveness and success of such platforms in deepwater conditions. For platforms in deeper waters, mooring lines generally contribute significant inertia and damping due to their longer lengths, larger sizes, and heavier weights. Accurate motion analysis of platforms in deep waters requires that these damping values be included. The most common approach for solving the dynamics of Spar platform is to employ a decoupled quasi-static method, which ignores all or part of the interaction effects between the platform and mooring lines. Coupled analysis, which includes the mooring lines and platform in a single model, is the only way to capture the damping from mooring lines in a consistent manner. The present coupling is capable in matching the forces, displacement, velocities and acceleration at the fairlead position along with all possible significant non-linearities. The output from such analyses will be platform motions as well as a detailed mooring line response. The computational efforts required for coupled system analysis considering a complete model including all mooring lines are substantial and should therefore mainly be considered as a tool for final verification purposes. In actual field problems hydrodynamic loads due to wave and currents act simultaneously on Spar platform and mooring lines. In finite element model, the entire structure acts as a continuum. This model can handle all non-linearities, loading and boundary conditions. The commercial finite element code ABAQUS/ AQUA is found to be suitable for the present study. The selected configuration of the offshore Spar platform is analysed under the regular wave loading and its structural response behavior in steady state is studied. The response of Spar-mooring system is obtained after 1 and 3 hours of storm. The result shows the effect of mooring line damping due to fully coupled analysis of Spar-mooring system.